2022
DOI: 10.1016/j.system.2022.102755
|View full text |Cite
|
Sign up to set email alerts
|

The interaction patterns of pandemic-initiated online teaching: How teachers adapted

Abstract: This study investigated how teachers adjusted their teaching practices for online teaching during the COVID-19 pandemic in Vietnam. In the study, we collected data from ten teachers within the Department of English at a university in Vietnam through semi-structured interviews via Zoom. During the interviews, the participants shared how they organised their teaching activities and addressed challenges in engaging students. To analyse the data, we focused on the variety of interaction patterns (teacher-student, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 48 publications
4
19
1
Order By: Relevance
“…This study demonstrated the DCE framework's value as a potential tool to enable researchers to have a deeper understanding of teachers' digital competence. Le et al (2022) focuses on how Vietnamese EFL teachers adjusted their online pedagogical practices to facilitate multiple forms of interaction. They were found to organize teaching activities for teacher-student interaction and student-content interaction but not for student-student interaction.…”
Section: The Special Collectionmentioning
confidence: 99%
“…This study demonstrated the DCE framework's value as a potential tool to enable researchers to have a deeper understanding of teachers' digital competence. Le et al (2022) focuses on how Vietnamese EFL teachers adjusted their online pedagogical practices to facilitate multiple forms of interaction. They were found to organize teaching activities for teacher-student interaction and student-content interaction but not for student-student interaction.…”
Section: The Special Collectionmentioning
confidence: 99%
“…The challenges faced by educators during the pandemic have led to recommendations for preparation programs and institutions to ensure teachers are prepared to teach using difference modalities and understand best practices for engaging students remotely Le, et al, 2022). Our teachers' experiences during this time period of not only Covid19 but also of increased awareness of societal inequities and social unrest demands more focused attention on not simply online teaching strategies but specifically on how to be a culturally responsive and abolitionist teacher in a virtual environment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on peer learning in relation to the integration of technologies during ERT are still rare. Le et al (2022) showed that teachers hoped for the support of a learning management system in courses, to provide peer support and mentoring, and for online communities to share their best practices. A study by Johnson et al (2020) showed that peer learning was a sought-after source of support and that it had clear benefits for teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have focused on peer learning in relation to the integration of technologies during ERT. In their study, Le et al (2022) reported the interaction patterns of pandemic-initiated online teaching and how teachers from the English department at a university in Vietnam adapted to the situation. Those authors collected data from ten teachers and reported that the teachers received limited online training and had to learn by themselves how to engage students remotely.…”
Section: Peer Learning Among University Teachers In Terms Of Digital ...mentioning
confidence: 99%